The Impact of High-Performance Work Systems (HPWS) on Employee Performance: A Multiple Mediation Approach Job Satisfaction and Job Engagement - Vayanti, Riyusni; Mon, Muhammad Donal (Riviera Publishing, 2025)
This study aims to analyze the influence of High Performance Work System (HPWS) on Employee Performance with Job Satisfaction and Job Engagement as the mediation variables, and Leadership as the moderation variable. Data was collected from 404 employees within the Riau Islands Provincial Government using a questionnaire distributed through Google Form. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study show that HPWS has a significant positive effect on Employee Performance both directly and through the mediation variables of Job Satisfaction and Job Engagement. Leadership has not been proven to moderate the influence of Job Satisfaction and Job Engagement on Employee Performance. This research provides empirical evidence on the importance of implementing HPWS in improving employee performance in the public sector. HPWS practices such as training and development, performance appraisals, and effective communication can increase job satisfaction and engagement, which will ultimately improve employee performance.